2008
DOI: 10.1577/t07-061.1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Stream Fish Assemblages with Niche Apportionment Models: Patterns, Processes, and Scale Dependence

Abstract: Abstract.-Understanding patterns in terms of the mechanistic processes that produce them is the essence of ecology. However, many studies merely document nonrandom patterns of species coexistence without providing insight into the structuring mechanisms and their scale dependence. Moreover, few studies address the mechanisms driving functional diversity. The objectives of this study were to document empirical patterns of species coexistence within stream fish assemblages across a broad geographic region, addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
(39 reference statements)
1
21
0
Order By: Relevance
“…However, some mechanisms are still little understood by ecologists, such as resource partitioning and other factors that allow the species to coexist (Esteves & Galetti, 1994;Gerking, 1994;Higgins & Strauss, 2008). Therefore, dietary analysis may reveal important information about trophic dynamics and resource partitioning among fish species (Ross, 1986), especially with regard to environments that are subject to sudden changes, such as streams (Johnson & Arunachalam, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, some mechanisms are still little understood by ecologists, such as resource partitioning and other factors that allow the species to coexist (Esteves & Galetti, 1994;Gerking, 1994;Higgins & Strauss, 2008). Therefore, dietary analysis may reveal important information about trophic dynamics and resource partitioning among fish species (Ross, 1986), especially with regard to environments that are subject to sudden changes, such as streams (Johnson & Arunachalam, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of the relationships among landscape, stream characteristics and fish assemblages has thus motivated several studies (e.g. Poff, 1997;Porter et al, 2000;Higgins and Strauss, 2008). Some of these studies indicated that fish assemblages can be structured not only by local processes, but also by large-scale environmental factors (Magalha˜es et al, 2002;Hoeinghaus et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the analysis of functional organization of fish assemblages allows characterizing different aspects of the community structure other than taxonomic organization (Hoeinghaus et al, 2007;Higgins and Strauss, 2008) and permit comparisons among broad geographic regions even when communities present different taxa (Simberloff and Dayan, 1991). In the Iberian Peninsula this approach will contribute to avoid problems related to spatially restricted endemisms.…”
Section: Mots-clésmentioning
confidence: 99%